Analisis Teknik Persuasi Dan Gaya Bahasa Iklan Pepsodent Di Media Televisi - Teti Siti Rohimah, Dihyah (2016)
This study has two objectives. Describing the persuasion techniques Pepsodent ad on television. Identify the language style form Pepsodent ad on television. This study uses qualitative descriptive object of this research is the language used in Pepsodent toothpaste ad on television. The data in this study a language used in the ad Pepsodent toothpaste. This research analyzed using techniques refer to the note. Methods of data analysis in this study using data analysis methods frontier. Method of presenting the results of the data analysis methods of presenting the data presented formally and informally. Based on the results of research conducted, it can be seen that in there Pepsodent ad persuasion techniques (1) rationalization, (2) identification, (3) suggestion, (4) conformity, and (5) compensation. A style that is contained in the ad Pepsodent namely (1) an apostrophe, (2) asidenton, (3) polisindeton, (4) eufemismus, (5) prolepsis or anticipated, (6) eroteris or a rhetorical question, and (7) the equation or simile ,